Talk Style Patterns and Use of Slang as Non-Standard Variety among MPBA Students at UIN Maulana Malik Ibrahim Malang - Taftinatul Ilmiyah; Sri Handayani; Fahma Hurrosatud Diyanah; Djoko Susanto (Al-Jawhar : Journal of Arabic Language, 2025)
This study examines talk style patterns and the use of slang as a non-standard variety among students in the Master’s Program in Arabic Language Education (MPBA) at UIN Maulana Malik Ibrahim Malang. This topic is important to study because the use of slang among students continues to evolve alongside the influence of digital media, while the MPBA community possesses unique characteristics as an academic group with high linguistic competence yet remains active in using non-standard varieties in daily communication. This study aims to describe the characteristics of MPBA students’ talk style, identify the forms of slang used, and analyze the relationship between talk style patterns and the use of slang in various communication contexts. The study employs a descriptive qualitative approach using data collection techniques such as observation, semi-structured interviews, and conversation documentation. Research informants were purposively selected from active MPBA students at UIN Maulana Malik Ibrahim Malang. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that MPBA students possess strong style-shifting abilities, adapting their speech style based on the situation, communication goals, and conversation partner. In formal contexts, students tend to use standard language, whereas in informal contexts, they use a more relaxed and expressive style. The forms of slang identified include Indonesian slang, Arabic–Indonesian slang, and English–Indonesian slang. The use of slang is more dominant in informal interactions and serves as a means of building closeness, solidarity, and group identity. The research findings confirm that the use of slang does not diminish students’ academic abilities but rather demonstrates sociolinguistic competence in selecting language varieties appropriate to the communicative context.